Exploring the influence of digital marketing strategies on private university selection - Tuna, Syifa Azzahra; Cahyani, Diah Hanung; Lantana, Dhieka Avrilia; Lestari, Rahayu (Global Advances in Business Studies, 2024)
Understanding the factors influencing students' decisions to attend private universities can provide valuable insights for educational institutions in South Jakarta. This study aims to determine the effects of aspects of digital marketing, such as social media, marketing, paid ads, and website quality, on students’ decision to select private universities in South Jakarta. If universities know which factors have the most significant impact, they can effectively allocate their resources. Data were collected through questionnaires distributed via Google Forms to first-year students across private universities in South Jakarta. This study used a purposive sampling technique to collect data from 101 respondents, and quantitative methods were used for analysis. The results show a positive correlation between the decision to attend a private university and social media marketing, influencer marketing, and paid ads.